2013
DOI: 10.1111/geb.12125
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock and density of northern boreal and temperate forests

Abstract: Aim To infer a forest carbon density map at 0.01°resolution from a radar remote sensing product for the estimation of carbon stocks in Northern Hemisphere boreal and temperate forests. LocationThe study area extends from 30°N to 80°N, covering three forest biomes -temperate broadleaf and mixed forests (TBMF), temperate conifer forests (TCF) and boreal forests (BFT) -over three continents (North America, Europe and Asia). MethodsThis study is based on a recently available growing stock volume (GSV) product retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
7
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(258 citation statements)
references
References 52 publications
(97 reference statements)
10
229
7
2
Order By: Relevance
“…-Northern boreal and temperate above-ground biomass (AGB) from the carbon stock and density map developed by Thurner et al (2014). This map is based on the growing stock volume (GSV) estimates obtained with the Biomasar algorithm using EN-VISAT ASAR images.…”
Section: Fuel Map Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…-Northern boreal and temperate above-ground biomass (AGB) from the carbon stock and density map developed by Thurner et al (2014). This map is based on the growing stock volume (GSV) estimates obtained with the Biomasar algorithm using EN-VISAT ASAR images.…”
Section: Fuel Map Assessmentmentioning
confidence: 99%
“…Many studies have shown continental differences within biogeographical regions, including species richness (Barthlott et al, 2007;Kreft and Jetz, 2007), total biomass Baccini et al, 2012;Banin et al, 2014;Thurner et al, 2014), and fire behavior (Lehmann et al, 2014;Rogers et al, 2015). Some of the most evident differences regarding vegetation behavior to fire were addressed with the inclusion of the regional GlobCover map to account for needle-leaved deciduous trees (Larix) in Asia (fuelbeds with land covers 92, 102, 112 and 122), and with the creation of specific fuelbeds for Australia with Eucalyptus vegetation (land covers 43, 113, 123 and 133).…”
Section: Fuelbed Mapmentioning
confidence: 99%
“…Instead we performed basic evaluation using an expertderived Potential Natural Vegetation (PNV) map and using remotely-sensed data sets of tree cover (Dimiceli et al, 2015), canopy height (Simard et al, 2011) and biomass (Avitabile et al, 2016;Thurner et al, 2014) to consider how LPJ-GUESS responds when EMAC climate is used as the forcing data. To provide an overall summary metric of data-model agreement across the relevant spatial domain, the Normalised Mean Error (NME) is presented following the prescription and recommendations…”
Section: Model Evaluationmentioning
confidence: 99%
“…We combined two biomass datasets, one tropical (Avitabile et al, 2016) and one northern temperate and boreal (Thurner et al, 2014), The coupled model simulates well the global patterns of biomass (Fig 3), but it does not capture the very high biomass observed in the tropical forests. This underestimation may be due to the use of pre-industrial nitrogen deposition data.…”
Section: Biomassmentioning
confidence: 99%
“…For instance, a C-band SAR signal is known to saturate rapidly with forest biomass because its wavelength is small (5-6 cm). However, using a hypertemporal series of C-band images, Santoro et al (2011) and Thurner et al(2014) were able to estimate the biomass of boreal and temperate forests. As part of the Copernicus mission from the European Space Agency (ESA), Sentinel-1A with C-band radar was successfully launched in April 2014 and will soon provide C-band imagery.…”
Section: Radio Detection and Ranging Technologymentioning
confidence: 99%